Comparative Analysis of Gasoline and Liquefied Petroleum Gas (LPG) on Motorcycle Engine Performance - Yamin, Octo Muhammad; Nasution, Devi Maiya Sari; Noer, Zikri; Lubis, Hariyati; Sofie, Tengku Machdhalie (Journal of Technomaterial Physics, 2024)
This research aims to determine the efficiency of LPG fuel performance compared to gasoline in motorcycle engines. The research method involves a brake dynamometer test with engine speed variations of 2000 rpm, 2200 rpm, and 2500 rpm. Based on the results obtained, the exhaust gas temperature (°C) at an engine speed of 2000 rpm with gasoline is 148°C and 146°C, while with LPG, it is 107°C and 108°C. The fuel consumption rate (cc/min) at 2000 rpm is 15.8 cc/min, 16.2 cc/min with gasoline, and 9.36 cc/min with LPG. At 2200 rpm, the fuel consumption is 16.2 cc/min, 22.8 cc/min with gasoline, and 10.48 cc/min with LPG. At 2500 rpm, it is 20.2 cc/min, 19.4 cc/min with gasoline, and 14.40 cc/min with LPG. In terms of fuel consumption savings, using LPG as a fuel can significantly reduce fuel usage.